Performance Analysis and Comparison Between Predictive Current and Predictive Torque Control Applied to a DFIG-DC System - de Lucena, Lucas F. M. (2025)
The expansion of DC microgrids has prompted investigations into wind energy systems to harness the benefits of this configuration. Therefore, this study aims to analyze and compare the performances of predictive current control (PCC) and predictive flux and torque control (PTC) applied to a doubly-fed induction generator which has its stator windings connected to a DC microgrid by means of a diode bridge. This system is commonly known as DFIG-DC. The system's performance was evaluated in terms of electromagnetic torque ripple, rotor flux ripple, and current distortion across a range of operating speeds. Although PCC and PTC applied to DFIG-DC have been discussed in previous works, a systematic comparison between them lacks in the literature, which is the main contribution of this paper. In addition, this work discusses the robustness of both methods under parametric errors of stator and rotor resistances, and magnetizing inductance, which has not been approached before.